Current approach to acute stroke management. Issue 4 (22nd April 2021) - Davies, Leo; Delcourt, Candice
Abstract: There have been marked improvements in the management of stroke in Australia over the past two decades. The greatest benefit has accrued from public health measures including reduced smoking rates and treatment of hypertension and hypercholesterolaemia. Recent advances in recanalisation therapy offer the chance of recovery to a subset of people who have a stroke. For many patients, stroke remains an illness with a devastating impact on their quality of life. Reducing the burden of stroke requires intervention across the health system from primary prevention through diagnosis, acute treatment, rehabilitation and secondary prevention. In this review, we will cover the changes in the epidemiology of stroke, public health measures in primary prevention of stroke, and acute management and secondary prevention of ischaemic stroke and primary intracerebral haemorrhage.